Efektifitas penggunaan aplikasi Quizizz dalam pembelajaran berbasis digital - Wahyudi, Adi (Maliki Interdisciplinary Journal, 2024)
The Quizizz application is one of the sites or applications commonly used by students both at the elementary, junior high, high school level, as well as students who continue their education in college. The use of this application is also not without reason, as for some reasons choosing quizziz as a learning medium such as the first to save time and costs so that the instructor only prepares questions in the application without making paper, the second to make students not bored in learning done with digital methods like that. The main purpose of using quizziz is to measure the ability of students who have received the material presented. But is this method effective in measuring students’ abilities. In this article the author will discuss the effectiveness of using quizzes as a learning media in digital media.